AntiThyroglobulin Antibody as a Prognostic Factor to Evaluate the Recurrence and Metastases of Differentiated Thyroid Carcinoma following Radioactive Iodine Ablation (Bangladesh Journal of Nuclear Medicine, 2022)
Objectives: Patients with Differentiated Thyroid Carcinoma (DTC) are usually treated with thyroidectomy followed by radioactive iodine ablation (RAIA). After treatment, during their follow up period, serum thyroglobulin (Tg) estimation and diagnostic whole body 131I scan (DxWBS) are established modalities to observe recurrence. The aim of this study was to evaluate the clinical significance of TgAb levels for possible use as a prognostic factor of recurrence and metastases of disease.Patients & Methods: An observational Cohort study was conducted in total 48 diagnosed DTC patients who underwent total thyroidectomy followed by RAIA during July, 2016 to June, 2017 at National Institute of Nuclear Medicine & Allied Sciences (NINMAS). Among them, 24 patients with high TgAb level (>40 IU/ml) were considered as group I and 24 DTC patients with low TgAb level (